High performance solid state supercapacitor based on a 2-mercaptopyridine redox-mediated gel polymer. Issue 29 (27th April 2015) - Sun, Kanjun; Dong, Miaomiao; Feng, Enke; Peng, Hui; Ma, Guofu; Zhao, Guohu; Lei, Ziqiang
<x xml:space="preserve">Abstract</x> A novel gel polymer PVA-H3PO4-PySH is prepared through introducing redox-mediated PySH into PVA-H3PO4 host, and a solid state supercapacitor is fabricated using the gel polymer as electrolyte and separator, activated carbons as electrodes.